Heat treatment on the multiple-impact mechanical responses and damage behaviors of 3D and 2D woven GF/PP/epoxy composites. (February 2023) - Pan, Zhongxiang; Zhao, Qinqin; Wei, Qingsong; Wu, Zhenyu; Li, Ni
Abstract: In this work, the 3D and 2D fabric reinforcements were made of glass/polypropylene (GF/PP) commingle filaments. The effect of heat treatment on the multiple impact mechanical responses and damage behaviors of GF/PP/epoxy composites were investigated. It is found that the pre-impact heat treatment (P) could maintain the best performance in the mechanical responses at the 3rd impact; The post-impact heat treatment (VH) could play the role of filler or healing agent after each impact load, but polypropylene fibers existing as reinforcement were melted into fusant and flowed out of the material along cracks, which results in reduction of mechanical properties. Under low-velocity impact, 3D woven composites were more sensitive to heat treatment because of the stress concentration of heated Z-binder yarns as the anti-delamination role; Perforation failure at the 3rd impact was found in the 3DOW structure with post-impact heat treatment, while the 2D woven laminated structure could still withstand more impacts. At high strain rates, heat treatment made polypropylene fibers be melted and recrystallized, and changed their volume and morphology, resulting in global micro voids in the material under impact load, which inhibits the formation of localized macro shear cracks. Highlights: Heat treatment makes PP fibers be melted, recrystallized and changed in morphology. Pre-impact heat treatment restrains crack propagation and maintains mechanical responses. Post-impact heat treatment fills cracks but results in reduction of mechanical properties. 2D woven laminates present better perforation resistance than 3DOW structures. Heat treatment results in global micro-voids but inhibits localized macro-shear cracks.